PERSEPSI SISWA KELAS VIII TERHADAP PEMBELAJARAN PJOK SECARA DARING DI SMP NEGERI 29 PEKANBARU - Doni Bastanta Sianturi; Ramadi Ramadi; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study aims to determine the Perceptions of Class Vlll Students towards Learning PJOK Online at SMP Negeri 29 Pekanbaru. Based on the results of the research, it shows that (1) the perception of class VIII students towards learning PJOK online on students' motivation in implementing physical education learning at SMP Ngeri 29 Pekanbaru, that there are 75 (56.39%) students who are in good criteria. (2) Perceptions of class VIII students towards learning PJOK online on the ability of teachers in implementing physical education learning at SMP Ngeri 29 Pekanbaru, that there are 96 (72.18%) students who are in very good criteria. (3) The perception of class VIII students towards online PJOK learning on the completeness of facilities and infrastructure in the implementation of physical education learning at SMP Ngeri 29 Pekanbaru, that there are 66 (49.62%) students are in very good criteria. Thus the perception of class VIII students towards learning PJOK online at SMP Negeri 29 Pekanbaru is seen from the overall data of sub-variables consisting of, a). Motivation, b). Orchestra Physical Education teacher, c). Facilities and infrastructure can be said to be quite good, with a percentage (59.40%) this result means that the perception of class VIII students towards learning PJOK online at SMP Negeri 29 Pekanbaru can run quite well.Key Words: Student Perception, PJOK Online Learning